School‐based systems change for obesity prevention in adolescents: outcomes of the Australian Capital Territory 'It's Your Move!'. (27th July 2017) - Malakellis, Mary; Hoare, Erin; Sanigorski, Andrew; Crooks, Nicholas; Allender, Steven; Nichols, Melanie; Swinburn, Boyd; Chikwendu, Cal; Kelly, Paul M.; Petersen, Solveig; Millar, Lynne
Abstract: Objective: The Australian Capital Territory 'It's Your Move!' (ACT‐IYM) was a three‐year (2012–2014) systems intervention to prevent obesity among adolescents. Methods: The ACT‐IYM project involved three intervention schools and three comparison schools and targeted secondary students aged 12–16 years. The intervention consisted of multiple initiatives at individual, community, and school policy level to support healthier nutrition and physical activity. Intervention school‐specific objectives related to increasing active transport, increasing time spent physically active at school, and supporting mental wellbeing. Data were collected in 2012 and 2014 from 656 students. Anthropometric data were objectively measured and behavioural data self‐reported. Results: Proportions of overweight or obesity were similar over time within the intervention (24.5% baseline and 22.8% follow‐up) and comparison groups (31.8% baseline and 30.6% follow‐up). Within schools, two of three the intervention schools showed a significant decrease in the prevalence of overweight and obesity ( p <0.05). Conclusions: There was some evidence of effectiveness of the systems approach to preventing obesity among adolescents. Implications for public health: The incorporation of systems thinking has been touted as the next stage in obesity prevention and public health more broadly. These findings demonstrate that the use of systems methods can be effective on a small scale.